Web-Based Depression Screening and Psychiatric Consultation for College Students: A Feasibility and Acceptability Study - Aya Williams; Rachel LaRocca; Trina Chang; Nhi-Ha Trinh; Maurizio Fava; Joseph Kvedar; Albert Yeung (International Journal of Telemedicine and Applications)
Background. A steady rise in the prevalence of depression among college students has negatively affected student quality of life. This study investigates the feasibility and acceptability of a Web-based model, including Skype, to screen and provide psychiatric consultation to depressed college students. Methods. Students completed the 9-item Patient Health Questionnaire (PHQ-9) online; those who screened positive (PHQ-9 ≥ 10) or endorsed any level of suicidal ideation were offered Web-based psychiatric consultation using Skype. After the consultation, students filled out a 7-item satisfaction questionnaire to report on the acceptability of this Web-based method. Results. A total of 972 students consented to the online depression screening and 285 screened positive. Of those, 69 students consented and 17 students successfully completed the psychiatric consultation via Skype. Thirteen (76.4%) students found the interview useful in helping them understand their depression. Fifteen (88.2%) students thought that psychologists and psychiatrists could successfully see patients via videoconferencing. Conclusions. Current online technologies can provide depression screening and psychiatric consultation to college students; those who participated reported a positive experience. Future studies will need to address the low levels of participation among college students and attract students who are underserved, as well as use a videoconferencing platform that adequately protects data confidentiality.